A Microphysiological Approach to Evaluate Effectors of Intercellular Hedgehog Signaling in Development - Johnson, Brian P.; Vitek, Ross A.; Morgan, Molly M.; Fink, Dustin M.; Beames, Tyler G.; Geiger, Peter G.; Beebe, David J.; Lipinski, Robert J. (Frontiers in Cell and Developmental Biology, 2021)
Paracrine signaling in the tissue microenvironment is a central mediator of morphogenesis, and modeling this dynamic intercellular activity in vitro is critical to understanding normal and abnormal development. For example, Sonic Hedgehog (Shh) signaling is a conserved mechanism involved in multiple developmental processes and strongly linked to human birth defects including orofacial clefts of the lip and palate. SHH ligand produced, processed, and secreted from the epithelial ectoderm is shuttled through the extracellular matrix where it binds mesenchymal receptors, establishing a gradient of transcriptional response that drives orofacial morphogenesis. In humans, complex interactions of genetic predispositions and environmental insults acting on diverse molecular targets are thought to underlie orofacial cleft etiology. Consequently, there is a need for tractable in vitro approaches that model this complex cellular and environmental interplay and are sensitive to disruption across the multistep signaling cascade. We developed a microplate-based device that supports an epithelium directly overlaid onto an extracellular matrix-embedded mesenchyme, mimicking the basic tissue architecture of developing orofacial tissues. SHH ligand produced from the epithelium generated a gradient of SHH-driven transcription in the adjacent mesenchyme, recapitulating the gradient of pathway activity observed in vivo. Shh pathway activation was antagonized by small molecule inhibitors of epithelial secretory, extracellular matrix transport, and mesenchymal sensing targets, supporting the use of this approach in high-content chemical screening of the complete Shh pathway. Together, these findings demonstrate a novel and practical microphysiological model with broad utility for investigating epithelial-mesenchymal interactions and environmental signaling disruptions in development.